The Influence Of The Use Of Accounting Information Systems, Qris-Based Digital Payments, And Financial Literacy On The Performance Of Small And Medium-Sized Enterprises - Zeylla Firanika Astuti; Merlyana Dwinda Yanthi (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to determine the effect of the use of Accounting Information Systems, QRIS-based digital payments, and financial literacy on the performance of culinary sector MSMEs in Surabaya City. This study uses a quantitative approach with primary data collected through questionnaires administered to MSME actors who have used accounting information systems and QRIS. The results indicate that Accounting Information Systems, QRIS-based digital payments, and financial literacy have a positive and significant impact on SME performance. These findings indicate that the use of a more structured financial recording system helps business actors generate more accurate financial information for decision making, the use of QRIS improves the smoothness and efficiency of transactions, and financial literacy strengthens the ability of MSME actors to prepare financial plans.